Investigating internet use by mental health service users: interview study. - Powell, J; Clarke, A (2007)
The internet is an increasingly important source of mental health-related information, and has the potential to be harnessed as a tool to support self-care and informed decision-making. Yet little is known about the motivations and attitudes of users. We therefore undertook a qualitative interview study with a purposive sample of mental health service users with internet experience, to explore issues with respect to mental health-related internet use. One of the prime motivations for online mental health seekers was to find experiential information from other people with similar problems. This information allowed users to know they were not alone, and to instill hope that others in the same situation had recovered. Benefits of the internet as an information source included convenience, privacy and anonymity. Problems related more to misuse of the internet rather than concerns over inaccuracy. Such qualitative work is important in an emerging research area to understand internet use better.